2022
DOI: 10.3389/fonc.2022.999843
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns and prognostic implications of tumor-infiltrating lymphocytes dynamics in early breast cancer patients receiving neoadjuvant therapy: A systematic review and meta-analysis

Abstract: PurposeHigh levels of tumor-infiltrating lymphocytes (TILs) are associated with better outcomes in early breast cancer and higher pathological response rates to neoadjuvant chemotherapy especially in the triple-negative (TNBC) and HER2+ subtypes. However, the dynamic changes in TILs levels after neoadjuvant treatment (NAT) are less studied. This systematic review and meta-analysis aimed to investigate the patterns and role of TILs dynamics change in early breast cancer patients receiving NAT.MethodsMedline, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…This may have been a consequence of a generalized influx of immune cells after NAC and/or the body's attempt to attenuate a heightened pro-inflammatory, anti-tumor response. Notably, we also observed an improved pathologic response to preoperative chemotherapy in a select subset of patients with the highest quartile of intratumoral-and stromal-infiltrating immune cells, supporting previous work demonstrating similar results in other NAC-treated carcinomas [46][47][48]. Nevertheless, given that distant metastases are the primary mode of failure for gastric cancer, there are evidently a multitude of mechanisms driving tumor immune evasion and progression that may be independent of the TILs that are associated with the primary tumor [49].…”
Section: Discussionsupporting
confidence: 90%
“…This may have been a consequence of a generalized influx of immune cells after NAC and/or the body's attempt to attenuate a heightened pro-inflammatory, anti-tumor response. Notably, we also observed an improved pathologic response to preoperative chemotherapy in a select subset of patients with the highest quartile of intratumoral-and stromal-infiltrating immune cells, supporting previous work demonstrating similar results in other NAC-treated carcinomas [46][47][48]. Nevertheless, given that distant metastases are the primary mode of failure for gastric cancer, there are evidently a multitude of mechanisms driving tumor immune evasion and progression that may be independent of the TILs that are associated with the primary tumor [49].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings that ERBB2 gene expression is strongly associated with pCR, but expression of immune genes is not, may be supportive of this idea. However, another explanation would be that TILs and immune gene expression in pretreatment biopsies may not be suitable predictors of potential immune activation, as it has been shown that the immune infiltrate is dynamic and changes during treatment are associated with outcome 38 . Studies evaluating TILs in on-treatment biopsies and in residual disease of patients with no https://doi.org/10.1038/s41523-024-00636-4 pCR, may help to better understand this dynamic state in HER2-positive disease.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in TILs during neoadjuvant treatment appears to be associated with better outcomes in TNBC. The survival benefit of higher levels of infiltration was demonstrated in a meta-analysis that analyzed studies that performed paired analyses of TILs density before and after NACT ( 75 ). The NeoTRIP study also demonstrated an increase in TILs after 1 cycle of neoadjuvant systemic therapy ( 76 ).…”
Section: Tils As a Prognostic Biomarker In Etnbcmentioning
confidence: 99%